Flexibility Protection of Copyright in Indonesia - Dijan Widijowati (Postgraduate of Jayabaya University, 2016)
Information technology developments with various functions of application has become public needs on performing activities of daily life. Information technology development and duplication have a positive contribution to human civilization in modern times, but has given distortion of copyright protection in Indonesia. Establishment Copyright Act No. 28 of 2014 is expected to provide protection originators without extinguish of information technology. Normative juridical approach used in this research to described descriptive analytical assessment phase which focuses on the assessment of secondary data. Data was collected with literature study to support the object assessment. The results showed that Copyright Act No. 28 of 2014, not be able to restrict application functions of user as protection for originators. Surveillance, prevention and control of information technology user and duplication should be done in an integrated manner with involvement of businesses and third parties who have the technological ability to control digital devices in the process of duplication.